SISTEM PENGEMBANGAN DAN PEMBINAAN PEGAWAI NEGERI SIPIL DI JEPANG - Anwar Sanusi, (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
Japan has a unique system of civil servant coaching and development. The National Personnel Authority, the National Institute of Public Administration, and the National Public Service Ethics Board are clearly and specifically in charge of maintaining the civil servants' performance, loyalty, and professionalism. The strong culture of giving rewards and punishments has become the key to the success of civil servant coaching and development. Asian countries should learn from this Japanese role model to be adapted to their own civil servant administrative mechanism.